Daya Serap Pembelian Gabah Lokal Terhadap Daya Produksi Petani (Studi Perum Bulog Sub-Divre Meulaboh) - Cut Nova Rianda (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
The agricultural sector is one of the strategic commodities in Aceh Province. Meulaboh is one area that has these commodities. Commodities can be seen from the majority of people using fertile land for agriculture. Not apart from the strategic commodities, farmers Meulaboh always faced the problem of post-production that is, the increase in income. The next problem is the increase of agricultural production which is cultivated by farmers, not yet become the guarantor of increasing farmer’s income. The reason is that in post agricultural production the market mechanism and the basic pricing of grain issued by the government in this case is Perum BULOG is very low. Therefore, this study will provide answers on the purchasing power of grain, the production power and the effect of grain purchasing power by Bulog to the production power of Meulaboh farmers. This research is a quantitative research conducted on society and Perum Bulog Sub-Divre Meulaboh. Data collection techniques through questionnaires, observation and documentation. Quantitative data is processed with the help of SPSS for windows version 17.0. The results showed that: 1) The absorption capacity of grain purchases in the Meulaboh community by Perum BULOG was 46 percent. This value is in accordance with the conditions that occur in farming communities that the absorption of purchases made by Perum BULOG is still low. 2) The agricultural production power of Meulaboh society is based on the descriptive statistic of spss that is 38 percent. This percentage is smaller because the purchase of grain at a normal price as set by the government is very rarely done by Perum BULOG, consequently the community sells to anyone who buys. 3) The influence of absorption capacity of grain purchases made by Perum BULOG (x) on the production power of Meulaboh peasants is 11.3 percent. The small influence that occurs between two variables, the absorption capacity of grain and farmer’s production power is caused by the lack of purchasing activities conducted by Perum BULOG, even the people have been disappointed because the purchasing of grain is done by the entrepreneurs with the cheap price under the set by the government.